Evaluating the Issues Facing Investment in (RAHA WA MARAH) Nursery school in Saudi Arabia - Aljunayby, Afrah Saad (Journal of Educational and Psychological Sciences, 2021)
Various challenges affect investment in Raha wa Marah Nursery School in Saudi Arabia. The declining investments into this level of education in Saudi Arabia form the foundation for our analysis. According to Pressley et al. (2009), though elementary education has been perceived as the core beginning of a successful education life, it suffers various hindrances that expose this sub-section of the entire education system to likely extinction or reduced importance.In forming a reliable and valid research on the factors that may be attributing to truncated investment in nursery education, Duncan and Magnuson (2013) suggest various methodologies which are applicable. Through interviews with resourceful stakeholders in primary education, the challenges that impede nursery education in Saudi Arabia are spelled out. An interview is an important tool to collect primary information about the subject matter since structured questions either written or verbal are important in permitting the respondent to answer the areas of interest only.In the course of our study, various factors are seen to impede investments in nursery education in Saudi Arabia. Since education is a capital intensive sector, an insufficient fund devoted to the government and private sector hinders development in kindergartens. Other social and political factors are also seen to discourage investments in this section of education. Such social demographic factors like fertility rate and mortality rate play a role in determining the promotion of investment in nursery schooling in Saudi Arabia.Low investment into nursery education in Saudi Arabia has been impacted by various challenges that ought to be addressed. Lack of enough funds to promote literacy education in the kindergarten calls for enough budgetary allocation to the Ministry of Education that could be used in promoting investment.
Keywords: evaluation; school; investment; leading; nursery; issues; trade; challenges; factors